Integrasi Proses Elektrokimia dan Adsorpsi Karbon Aktif untuk Pengolahan Lindi Tempat Pemrosesan Akhir Sampah - Muhsinun Muhsinun; Lalu Auliya Akraboe Littaqwa (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study evaluated the performance of an integrated electrochemical and activated carbon adsorption process for the treatment of landfill leachate. The initial leachate characteristics showed a COD of 4,850 mg/L, color intensity of 6,200 Pt Co, and ammonia concentration of 780 mg/L, with a low BOD/COD ratio indicating poor biodegradability. The electrochemical process operated at an optimum current density of 20 mA/cm² achieved 46.3 percent COD removal and 62.5 percent color reduction within 120 minutes, with an energy consumption of 18.4 kWh/kg COD removed. Standalone adsorption using 20 g/L of activated carbon reduced COD by 38.7 percent and color by 71.2 percent within 150 minutes; however, adsorption capacity declined by 35 percent after two cycles without regeneration. The integrated system operated at pH 6, current density of 20 mA/cm², and 120 minutes hydraulic retention time achieved 78.9 percent COD removal, 91.4 percent color removal, and 64.8 percent ammonia reduction. The specific energy consumption decreased to 12.6 kWh/kg COD removed, demonstrating improved energy efficiency compared to the electrochemical process alone. In situ electrochemical regeneration conducted for 30 minutes at 30 mA/cm² restored up to 87 percent of the initial adsorption capacity after three operational cycles. These results confirm a significant synergistic effect between electrochemical oxidation and activated carbon adsorption, leading to enhanced treatment efficiency and operational stability for complex landfill leachate.